(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this study, GIS technique and remote sensing data have been integrated to createa suitability map for the probable sites of water harvesting in Badrah-Wasit, EasternIraq.Hydrological analysis used to find the potential water-harvesting sites, as well as to improve the water resource management. In this research, five criteria have been used, which is astream order, slope, distance to roads, rainfall and Normalized Difference Vegetation Index. These thematic layerswere evaluated with the multi-criteria analysis method, then combine and process together using weighted overlay method, then assigned suitable weights and integrated into a GIS to generate a suitability map.As a result, the region has been classified into three zones: high suitability zone (2%), moderate suitability zone (27%), and low suitability zone (35%) depending on the specific criteria used for this purpose and have high potential in terms of their suitability for water harvesting.